A critical review on studies of relationship education in the gender equity education of Taiwan: 10 years and beyond. Issue 3 (3rd July 2017) - Yang, Hsing-Chen; You, Mei-Hui
Abstract: With discourse analyses, this paper attempts to review the research development of relationship education in Taiwan for nearly a decade after the Gender Equity Education Act was announced in 2004, including the research topics generated, the knowledge accumulated, and the results achieved. This paper focuses not only on how the power and impacts of the academic institutions evolves through the production process of knowledge from the research, but also on how the gender perspectives are placed or filled into the discourses. Tracking and reflecting on the discourses and the development of relationship education researches in Taiwan, this paper aims to examine the interwoven effects and influences that social cultures, structures, and institutional power play on the knowledge production and research development of relationship education. The trajectory of Taiwanese experience illustrates a good example for policy making and legislative initiatives in legislative procedures in regard to certain gender knowledge and subjects. It is essential to utilize and coordinate the national resources and academic institutions with further awareness for the direction and promotion of gender knowledge in order for the education and research to root, grow, and prosper.